The Influence of Blue Ocean Strategy on Consumer Buying Interest (A Study On Richeese Factory Lhokseumawe City) - Nurrasyidah, Nurrasyidah; Iryani, Lisa; Maisyura, Maisyura; Ritonga, Nursakinah; Ameliany, Nanda (LPPM UIKA Bogor, 2024)
This study uses a quantitative approach which aims to determine Blue Ocean Strategy has a Positive and Significant influence on Consumer Purchase Interest. The population in this study were all Richeese Factory consumers in Lhokseumawe City and the determination of the sample using the “simple random sampling” method and the formula used in determining the number of respondents using the Lemesshow formula so that the number of respondents was 96 consumers. In proving and analyzing this, validity and reliability tests, classical assumption tests, simple linear regression tests and t tests (partial) are used. Statistically, this value gives the understanding that 51.4% of Blue Ocean Strategy variables affect consumer buying interest at Richeese Factory Lhokseumawe. This means that Richeese Factory Lhokseumawe's Consumer Purchase Interest will be influenced by the Blue Ocean Strategy in accordance with the equation Y = 5.563 + 0.901x.